Design and Development of Atenolol Matrix Tablet Employing Natural and Synthetic Polymers - Adity Bhowmik, Rajia Sultana Nijhu , Tajnin Ahmed, Sharmin Sultana (Journal of Applied Pharmaceutical Science, 2013)
The main objective of the present work was to develop sustained release matrix tablets of Atenolol. To reduce the frequency of administration and to improve the patient compliance, a once daily sustained release formulation of Atenolol is desirable. So sustained release Matrix Tablet of Atenolol was designed by using different polymers viz.Starch, Xanthan Gum, Vee Gum , Guar Gum, Gum Accacia, Tragacanth, Hupu Gum were used as natural polymers and Eudragit-L100, Ethyl Cellulose, Sodium Carboxy Methyl Cellulose (Na-CMC) ,Hydroxy Propyl Methyl Cellulose (HPMC) (5&15cps), Methyl Cellulose, Kollidon were used as synthetic polymers. After fixing the ratio of drug and polymer for control the release of drug up to desired time, the release rates were modulated by Single polymer, combination of two different rates controlling material. The FT-IR study revealed that there was no chemical interaction between drug and excipients. The granules were prepared by dry granulation method. Precompressional parameters i.e. angle of repose, percent compressibility, and Hausner’s ratios were studied. These results indicate that granules are good flowing characteristics. After evaluation of physical properties like Weight variation, Hardness, Thickness, Friability of tablet, the different formulations checked for the Percentage Drug content which having good uniformity. The results of drug dissolution studies showed improved drug release, retardation effects of the polymers and could achieve better performance. After eight hours dissolution test, dissolution profiles showed that better sustained release was observed from starch and veegum containing formulation and eudragit and ethyl cellulose containing formulation of atenolol matrix tablet. It was also observed that the presence of starch caused an increase in the release rate of atenolol matrix tablet. The present study shows a relatively simple method to design and develop Atenolol matrix tablet.
Keywords: Atenolol matrix tablet, Xanthan Gum, Gum Accacia,Tra